In-situ gel electrolyte for aqueous zinc ion capacitor and preparation method and application thereof
By using graphene oxide as an ultraviolet initiator in zinc ion capacitors to form an in situ gel electrolyte, the problems of dendrite growth, hydrogen evolution corrosion and poor interfaces in zinc ion capacitors during use are solved, and higher performance stability and lower cost are achieved.
Patent Information
- Application Number
- CN202411665782.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-20
AI Technical Summary
During the use of existing zinc ion capacitors, there are problems such as dendrite growth, hydrogen evolution corrosion and poor electrolyte-electrode interface, resulting in unstable performance and high cost.
Graphene oxide is used as the ultraviolet initiator, and it is uniformly dispersed into the organic polymer monomer and zinc brine solution by magnetic stirring and ultrasonic dispersion to form a precursor dispersion liquid, and polymerization is initiated on the surface of the zinc foil by ultraviolet irradiation to form an in situ gel electrolyte.
The problem of stable interface and low interface impedance are achieved, slowing down dendritic growth and hydrogen evolution corrosion is improved, the performance and stability of zinc ion capacitors are simplified, and the process is reduced and costs are reduced.
Smart Images

Figure CN119742186A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gel electrolytes, and in particular to an in-situ gel electrolyte for aqueous zinc ion capacitors and a preparation method and application thereof. Background Art
[0002] In recent years, with the increasing shortage of fossil fuels and environmental pollution, people are increasingly in need of energy storage devices with high energy / power density, high safety and low cost. Hybrid capacitors, which combine the advantages of capacitors and metal ion batteries, have attracted widespread attention. In particular, zinc ion capacitors have obvious advantages in high energy density and low cost.
[0003] However, the use of zinc metal as the negative electrode of hybrid capacitors currently has serious problems such as dendrite growth, hydrogen evolution corrosion, and the generation of inactive byproducts. The use of polymer gel electrolytes can alleviate the above problems to a certain extent, but polymer gel electrolytes themselves still have problems such as complex preparation process, low ion transfer efficiency, and poor electrolyte-electrode interface, which hinder their practical application. Patent CN113782844B discloses a method for preparing a hydrogel electrolyte for an aqueous zinc ion energy storage battery. This method adopts a method of heating polymerization and then immersing the electrolyte, which has a complex process and poor electrochemical performance; and patent CN118213636A discloses a method for preparing a transparent and flexible zinc ion hydrogel electrolyte, which also adopts a thermally initiated polymerization method, has a complex process, and has poor mechanical and electrochemical properties.
[0004] Therefore, it is necessary to develop a convenient, efficient, environmentally friendly, and low-cost process to prepare gel electrolytes with stable interfaces and high ion transfer efficiency for high-performance zinc ion capacitors to promote their industrial application. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an in-situ formed gel electrolyte and its application in a zinc ion capacitor in order to solve the above problems. The method uses graphene oxide as a UV initiator with stable structure, non-toxicity, pollution-free and low cost. By ultraviolet irradiation, the oxygen-containing groups on the graphene oxide fall off to form free radicals, thereby guiding the organic polymer monomers to polymerize into chains, and under the condition that the crosslinking agent monomer participates in the reaction, a gel network is formed on the surface of the zinc foil. The method of the present invention is simple and effective, with rapid forming and stable interface.
[0006] At the same time, the present invention also provides the application of the in-situ gel electrolyte.
[0007] The purpose of the present invention is achieved by at least one of the following technical solutions.
[0008] The first aspect of the present invention is to provide a method for preparing an in-situ gel electrolyte, comprising the following steps:
[0009] (1) using a magnetic stirring method and an ultrasonic dispersion method to uniformly disperse graphene oxide in a zinc salt aqueous solution containing an organic polymer monomer and a crosslinking agent monomer to obtain a precursor dispersion;
[0010] (2) uniformly coating the precursor dispersion on the surface of the zinc foil from which the oxide has been removed;
[0011] (3) The precursor dispersion is polymerized on zinc foil by ultraviolet irradiation to obtain an in-situ gel electrolyte.
[0012] The method for preparing the in-situ gel electrolyte according to the first aspect of the present invention has at least the following beneficial effects:
[0013] The present invention utilizes graphene oxide as a photoinitiator to generate free radicals and then guide the polymerization of organic polymer monomers. Graphene oxide as a photoinitiator has the properties of being stable, non-toxic and pollution-free. The precursor dispersion is directly polymerized on the surface of the zinc foil to form a gel electrolyte, and the electrolyte-electrode interface is stable and the interface impedance is low. The method of the ultraviolet in-situ molding gel electrolyte is simple and efficient, the reaction conditions are mild, and the controllability is strong. The graphene oxide remaining in the gel electrolyte after molding is stable, and the oxygen-containing functional groups that have not been separated can regulate the electric field distribution inside the gel electrolyte due to their affinity with zinc ions, thereby effectively slowing down the growth of zinc dendrites.
[0014] In some embodiments of the present invention, the zinc salt comprises one or more of zinc sulfate, zinc chloride, zinc perchlorate, and zinc acetate; preferably, the zinc salt is zinc sulfate; the concentration of the zinc salt aqueous solution is 0.5 to 6 mol kg -1 ; The organic polymer monomer includes one or more of acrylamide monomers, acrylate monomers, styrene monomers, and methyl methacrylate monomers; preferably, the organic polymer monomer is an acrylamide monomer; the ratio of the organic polymer monomer to the zinc salt aqueous solution is (1-3) g:10 mL, the mass of the cross-linking agent is 1-2% of the mass of the organic polymer monomer, preferably, the cross-linking agent is N,N'-methylenebisacrylamide.
[0015] In some embodiments of the present invention, the graphene oxide sheet has a diameter of 50 nm to 5 μm, and a mass of 0.5 to 5% of the mass of the acrylamide monomer.
[0016] In some embodiments of the present invention, the zinc foil may be in a square, round or other shape; the method of removing the oxide may be one or more of grinding and polishing or acid immersion; the grinding and polishing may utilize tools such as sandpaper, a grinder, and a polishing machine; the acid immersion may utilize one or more of hydrochloric acid, sulfuric acid, acetic acid, and citric acid, with a concentration of 5 to 20%.
[0017] In some embodiments of the present invention, the ultraviolet light wavelength of the ultraviolet irradiation method is 300-400 nm, the ultraviolet light source power is 5-120 W, and the irradiation polymerization time is 0.5-2 h.
[0018] The second aspect of the present invention is to provide an in-situ gel electrolyte prepared by the above method.
[0019] The third aspect of the present invention is to provide a zinc ion capacitor containing the above-mentioned in-situ gel electrolyte.
[0020] In some embodiments of the present invention, the zinc ion capacitor with in-situ gel electrolyte includes the above-mentioned zinc foil and the in-situ gel electrolyte formed thereon, and a positive electrode plate with capacitive properties; the positive electrode plate and the zinc foil sandwich the gel electrolyte in the middle to form a sandwich structure, which is finally packaged into a zinc ion capacitor.
[0021] In some embodiments of the present invention, the positive electrode sheet can be coated or formed onto a conductive substrate by coating, coiling, spraying or other processes. The electrode slurry is composed of an electrode material, a conductive additive and a binder. The electrode material can be an activated carbon material or one or more metal oxides such as vanadium pentoxide and manganese dioxide. The conductive additive can be carbon black such as Super P and acetylene black. The binder can be a polymer binder such as PVDF, PVA, and PVP. The conductive substrate can be made of materials such as aluminum foil, copper foil, stainless steel foil, carbon paper, and carbon cloth.
[0022] In some embodiments of the present invention, the packaging method can be button battery case packaging or soft package packaging.
[0023] The fourth aspect of the present invention is to provide a method for manufacturing the above-mentioned zinc ion capacitor, comprising the following steps.
[0024] (1) coating the precursor dispersion on the negative electrode sheet and the positive electrode sheet respectively, and irradiating them with ultraviolet light until they are in a semi-formed state, which is manifested in that the fluidity of the precursor dispersion becomes low and the inverted electrode sheet does not drip;
[0025] (2) Reversing the negative zinc sheet to cover the positive electrode, and continuing to irradiate the side with ultraviolet light until it is fully formed to obtain a sandwich structure;
[0026] (3) The obtained sandwich structure is packaged and tested.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) Compared with traditional initiators, such as persulfides, acrylates, ketone amines, benzophenone derivatives, etc., some of these initiators have poor water solubility, some are unstable and easy to decompose. In the present invention, graphene oxide is used as a photoinitiator, which is stable, non-toxic and pollution-free. In addition, due to the rich oxygen-containing groups on the carbon skeleton of graphene oxide, it has good water solubility; after gel polymerization, the flake graphene oxide is evenly distributed inside the gel, and the retained oxygen-containing groups have the characteristics of affinity for zinc ions, which can further form ion channels, regulate the zinc ion transmission path, reduce internal impedance, and improve ionic conductivity.
[0029] (2) Compared with the non-in-situ gel polymerization process, the present invention uses an in-situ polymerization process. The in-situ polymerization process is simple, the interface is stable, the interface impedance is low, the growth of dendrites is slowed down, and the problems of hydrogen evolution corrosion and electrode passivation caused by high water content of the gel are reduced.
[0030] (3) Compared with the thermally initiated polymerization process, the present invention uses the process of ultraviolet initiated polymerization, which is highly efficient and controllable, and has good gel forming quality. In addition, ultraviolet polymerization can achieve the positioning and regulation of the polymerization reaction through precise control of the light source, and can also avoid the possible impact of high temperature on the electrolyte or other components, is not easily affected by changes in environmental conditions or fluctuations in control conditions, and has high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the preparation process of UV in-situ gel electrolyte based on zinc foil;
[0032] Figure 2 This is a physical picture of the UV in-situ gel electrolyte based on zinc foil;
[0033] Figure 3 is the SEM image of the in-situ gel electrolyte;
[0034] Figure 4a is the electrode-electrolyte interface diagram of Example 1;
[0035] Figure 4b is the electrode-electrolyte interface diagram of Comparative Example 1;
[0036] Figure 5 Graphs of initial deposition potentials of Example 1 and Comparative Example 1;
[0037] Figure 6 The constant current charge and discharge (1 mA cm) of Example 1 (a) and Comparative Example 1 (b) -2 / 1mAh cm -2 ) Long cycle test diagram;
[0038] Figure 7a 1mA cm-2 / 1mAh cm -2 Surface morphology of zinc negative electrode of Example 1 after 100h of cycling;
[0039] Figure 7b 1mA cm -2 / 1mAh cm -2 Surface morphology of zinc negative electrode of comparative example 1 after 100h of cycling;
[0040] Figure 8 Cyclic voltammetry curves of the zinc ion capacitors of Example 2 and Comparative Example 2 (scan rate 30 mV s -1 );
[0041] Fig. 9 Long cycle test (current density 1A g) of the zinc ion capacitor of Example 2 and Comparative Example 2 -1 );
[0042] Figure numerals: zinc foil 1, in-situ gel electrolyte precursor dispersion 2, in-situ gel electrolyte 3, ultraviolet light source 4; step ① uniformly coating the precursor dispersion on the zinc foil, step ② ultraviolet irradiation method until the precursor is gelled. DETAILED DESCRIPTION
[0043] The present invention will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0044] Example 1
[0045] This embodiment 1 provides a UV-triggered in-situ polymer gel electrolyte, and uses it to assemble a button-type zinc symmetrical battery. The specific operation steps are as follows:
[0046] (1) 0.5 g acrylamide (AM) and 2.5 mg N,N-methylenebisacrylamide (MBA, crosslinker) were dissolved in 5 mL 1 M zinc sulfate (ZnSO4) electrolyte and stirred for 30 min; 5 mg graphene oxide (GO) with a flake size of 50-200 nm was added to obtain a mixed solution; the obtained mixed solution was magnetically stirred for 3 h and ultrasonically treated for 1 h to obtain a uniformly dispersed precursor dispersion.
[0047] (2) Take two pieces of zinc foil (diameter The surface of the zinc foil was polished with 2000-mesh sandpaper, and then immersed in 10% hydrochloric acid solution until uniform bubbles were generated on the surface of the zinc foil. The zinc foil was rinsed with deionized water and dried with dust-free paper to obtain the treated zinc foil. 100 μL of the precursor dispersion obtained in step (1) was respectively taken and evenly dripped on the surface of the treated zinc foil. The zinc foil was irradiated with an ultraviolet lamp (365 nm, 60 W) for 10 minutes to make the precursor dispersion polymerize in situ on the zinc foil but not completely polymerize, and attached to the zinc foil with a certain viscosity.
[0048] like Figure 2 As shown, the rheological properties of the precursor dispersion coated on the zinc foil are significantly reduced after UV irradiation, and it can be picked up with tweezers and adhered to the zinc foil.
[0049] (3) Invert one of the zinc foils with the incompletely polymerized precursor dispersion obtained in step (2) and cover it on the other zinc foil to fully mix the dispersion between the two zinc foils. Irradiate the two foils from the side with an ultraviolet lamp for 10 minutes to completely polymerize the two foils.
[0050] like Figure 3 As shown, the SEM image of the UV in-situ gel electrolyte shows an interconnected pore structure and a network structure.
[0051] like Figure 4a As shown, the SEM cross-sectional image of the UV in-situ gel electrolyte shows a close electrode-electrolyte interface. Figure 4b There is an obvious gap between the non-in-situ gel electrolyte and the electrode caused by moderate heat.
[0052] (4) The in-situ Zn||Zn structure was obtained and assembled into a symmetrical battery (CR2025).
[0053] Performance Testing
[0054] The initial deposition potential diagram of the symmetrical battery of Example 1 is obtained by measurement. Figure 5 As shown, it is 0.0684V, and the comparative example 1 is 0.0985V. Figure 6 Shown is 1mA cm -2 / 1mAh cm -2 According to the long cycle test diagram below, Example 1 ran stably for 4100 hours, while the voltage of Comparative Example 1 was unstable and varied greatly during the cycle process, and it failed due to a short circuit in less than 1100 hours. Figure 7a and Figure 7b 1mA cm -2 / 1mAh cm -2 After 100 hours of cycling under the test conditions, the surface electron microscope image of the zinc foil obtained by peeling off the gel is shown in the figure below. Figure 7a As shown, the deposition state of Example 1 is good, showing a dense, uniform and flat lamellar shape, while Figure 7bComparative Example 1 exhibits loose, inclined or upright intercalation.
[0055] Example 2
[0056] This embodiment 2 provides a UV-induced in-situ polymer gel electrolyte, and uses it in assembling a button-type zinc ion capacitor. The preparation process is as follows: Figure 1 The specific steps are as follows:
[0057] (1) Weigh 0.1 g of polyvinylidene fluoride (PVDF), add it to 1 mL of N-methylpyrrolidone (NMP), and mix it evenly in a planetary centrifugal mixer to obtain a viscous liquid; weigh 0.2 g of conductive carbon black (Super P) and 0.7 g of activated carbon (AC), grind them in a mortar, mix them evenly, and obtain a powdery mixture, add it to 4 mL of N-methylpyrrolidone (NMP), and mix it evenly in a planetary centrifugal mixer to obtain a dispersion; the viscous liquid obtained by mixing and the obtained dispersion are further mixed evenly in a planetary centrifugal mixer to obtain a coating slurry.
[0058] (2) The slurry obtained in step (1) was evenly coated on aluminum foil with a coating thickness of 150 μm. After coating, it was transferred to a vacuum oven and vacuum dried at 80° C. for 24 hours. The obtained product was then punched into diameters of The obtained AC positive electrode sheet was immersed in a 1M ZnSO4 electrolyte solution for 6 hours to ensure that the electrolyte solution completely penetrated the electrode sheet.
[0059] (3) Further, the same steps were used to prepare an in-situ gel electrolyte and assembled into a zinc ion capacitor. The difference between Example 2 and Example 1 is that one of the zinc foils in step (2) of Example 1 was replaced with the AC positive electrode obtained in step (2) of Example 2, and finally an in-situ Zn||AC structure was obtained, which was assembled into a zinc ion capacitor (CR2025).
[0060] Performance Testing
[0061] like Figure 8 The scan rate is 30 mV s -1 The cyclic voltammetry curve of Example 2 at 30mVs -1 280.4F g -1 The specific capacity is higher than that of comparative example 2, which is 217.4 F g -1 .like Fig. 9 The current density is 1A g -1 In the long cycle test, Example 2 ran for more than 1800 cycles, and the specific capacity remained at the initial capacity (172.6 mAh g -1) was 98.4%, and the Coulomb efficiency remained at 92.4%, while Comparative Example 2 failed after about 800 cycles.
[0062] Comparative Example 1
[0063] This comparative example 1 relates to a thermally initiated non-in-situ polymer gel electrolyte, and is used to assemble a button-type zinc symmetrical battery. The specific operation steps are as follows:
[0064] (1) Weigh 0.5 g AM, 2.5 mg MBA and 5 mg potassium persulfate (KPS) and dissolve them in 5 mL 1 M ZnSO4 solution to form a precursor solution. Inject the precursor solution into a glass mold (diameter The resulting mixture was heated in an oven at 60°C for 2 hours to obtain a gel electrolyte.
[0065] (2) The pretreated zinc foil is used as the two electrodes and sandwiched on both sides of the gel electrolyte obtained in step (1) to form a Zn||Zn structure and assembled into a symmetrical battery (CR2025).
[0066] Comparative Example 2
[0067] This comparative example 2 relates to a thermally initiated non-in-situ polymer gel electrolyte, and is used to assemble a button-type zinc ion capacitor. The specific operation steps are as follows:
[0068] The difference between this comparative example 2 and example 2 is that the in-situ formed gel electrolyte in example 2 is replaced with the gel electrolyte obtained in step (1) of comparative example 1 to obtain a Zn||AC structure, which is assembled into a zinc ion capacitor (CR2025).
[0069] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an in-situ gel electrolyte for an aqueous zinc ion capacitor, characterized in that: The following steps are involved: (1) using a stirring method and an ultrasonic dispersion method to uniformly disperse graphene oxide in a zinc salt aqueous solution containing an organic polymer monomer and a crosslinking agent monomer to obtain a precursor dispersion; (2) uniformly coating the precursor dispersion on the surface of the zinc foil from which the oxide has been removed; (3) The precursor dispersion is polymerized on zinc foil by ultraviolet irradiation to obtain an in-situ gel electrolyte.
2. The method for preparing an in-situ gel electrolyte for an aqueous zinc ion capacitor according to claim 1, characterized in that: In step (1), the zinc salt in the zinc salt aqueous solution includes one or more of zinc sulfate, zinc chloride, zinc perchlorate, and zinc acetate; the concentration of the zinc salt aqueous solution is 0.5 to 6 mol kg -1 ; The organic polymer monomer includes one or more of acrylamide monomers, acrylate monomers, styrene monomers, and methyl methacrylate monomers; the ratio of the organic polymer monomer to the zinc salt aqueous solution is (1-3) g:10 mL, and the mass of the crosslinking agent monomer is 1-2% of the mass of the organic polymer monomer.
3. The method for preparing an in-situ gel electrolyte for an aqueous zinc ion capacitor according to claim 1, characterized in that: In step (1), the diameter of the graphene oxide sheet is 50 nm to 5 μm, and the mass of the graphene oxide is 0.5 to 5% of the mass of the organic polymer monomer.
4. The method for preparing an in-situ gel electrolyte for an aqueous zinc ion capacitor according to claim 1, characterized in that: In step (2), the oxide removal method is one or more of grinding and polishing or acid leaching; the acid leaching uses one or more of hydrochloric acid, sulfuric acid, acetic acid, and citric acid; the mass percentage concentration of the acid is 5% to 20%.
5. The method for preparing an in-situ gel electrolyte for an aqueous zinc ion capacitor according to claim 1, characterized in that: In step (3), the wavelength of ultraviolet light in the ultraviolet irradiation method is 300-400nm, the power of the ultraviolet light source is 5-120W, and the irradiation polymerization time is 0.5-2h.
6. An in-situ gel electrolyte for aqueous zinc ion capacitors prepared by the preparation method according to any one of claims 1 to 5.
7. A zinc ion capacitor, characterized in that: The zinc ion capacitor comprises the in-situ gel electrolyte according to claim 6.
8. The method for manufacturing the zinc ion capacitor according to claim 7, characterized in that: The preparation method comprises the following steps: (a) coating the precursor dispersion on the negative electrode sheet and the positive electrode sheet respectively, and using ultraviolet irradiation method to a semi-formed state, which is specifically manifested in that the fluidity of the precursor dispersion becomes low and the precursor dispersion does not drip when the electrode sheet is inverted; (b) The negative electrode of the zinc sheet is reversed and placed on the positive electrode sheet, and the side is continuously irradiated with ultraviolet light until it is completely formed to obtain a sandwich structure; (c) The resulting sandwich structure was packaged and tested.
9. The method for manufacturing a zinc ion capacitor according to claim 8, characterized in that: The positive electrode plate is coated or formed by coating or rolling the electrode slurry onto a conductive substrate by a coating method, a coiling method or a spraying method; the electrode slurry is composed of an electrode material, a conductive additive and a binder, and the electrode material is an activated carbon material or one or more of vanadium pentoxide and manganese dioxide metal oxides; the conductive additive is one or more of Super P and acetylene black; the binder is one or more of PVDF, PVA, and PVP polymer binders, and the conductive substrate is made of aluminum foil, copper foil, stainless steel foil, carbon paper or carbon cloth material.
10. The method for manufacturing a zinc ion capacitor according to claim 8, characterized in that: The packaging method uses button battery case packaging or soft package packaging.
Citation Information
Patent Citations
A method for preparing a hydrogel electrolyte for an aqueous zinc ion energy storage battery
CN113782844B
Cross-linked solid electrolyte as well as preparation method and application thereof
CN113193228A
Gel electrolyte and composition thereof, flexible lithium ion battery and preparation method of flexible lithium ion battery
CN114069036A
Preparation of flexible conductive high-temperature-resistant hydrogel and application of flexible conductive high-temperature-resistant hydrogel in flexible zinc ion battery
CN115612123A
Preparation method of modified cellulose / graphene oxide composite gel electrolyte
CN118156594A